EVALUATION OF MOTILITY OF THE SHORT-TERM CRYOPRESERVED SPERM OF THE AFRICAN GIANT CATFISH (CLARIAS GARIEPINUS BURCHELL, 1822) - OYELEYE , O. O.; OMITOGUN, O. G. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
The motility of African giant catfish (Clarias gariepinus Burchell, 1822) sperm cryopreserved at -35o using different cryoprotectants were investigated. The study was carried out in the rainy season between June and September 2005. Ten percent (10%) of each of three permeating cryoprotectants: methanol, glycerol and dimethyl sulfoxide (DMSO); with 15% non-permeating cryoprotectant (skim milk) and 75% phosphate-buffered saline (PBS) as extender were used to prepare three different types of cryoprotectant combinations. The milt which was mixed with cryoprotectants at the ratio 1:1 and stored in 2 ml cryotubes was short-term cryopreserved in a deep freezer at -3.5o. The sperm was then revived at various intervals to evaluate the effect of cryoprotectants and periods of cryopreservation on its viability and motility. The results showed that the type of cryoprotectant combination had significant effect on sperm motility (p<0.05). Cryoprotectant combinations containing glycerol-preserved sperm better than those with DMSO and methanol in that order. This result demonstrated that short-term cryopreservation technique could be used as method of storage and management of sperm of the African catfish especially in Nigeria where supply of male brood stock is limiting.